OPTIMIZATION ISO 25010 WITH THE VORD METHOD AND C4.5 ALGORITHM IN SAVING LOAN COOPERATIVE - Subkhi, Akhmad Yunus; Andrianingsih, Andrianingsih; Lantana, Dhieka Avrilia (Jurnal Teknik Informatika (Jutif), 2023)
Advances in technology have made many companies and agencies, especially cooperatives, use information technology for their operational activities. Not infrequently in the operation of its business cooperatives have several obstacles caused by data processing and loan decision making still using conventional models. Cooperatives need a computerized information system in achieving organizational goals. To overcome this problem, a system is created that is integrated in one database which will be implemented by the Cooperative to facilitate its business operations. This study uses the Viewpoint Oriented Requirement Definition (VORD) method to analyze system requirements based on the user's point of view. In addition, the C4.5 Algorithm and the Naïve Bayes Algorithm as decision making for loan approval which will be compared in recommending and classifying loans using the confusion matrix, the results of testing the two algorithms with an accuracy value of the C4.5 Algorithm of 88.00% and an accuracy rate of the Naïve Bayes Algorithm of 76.00%. It can be concluded that the accuracy value of the C4.5 Algorithm is feasible to be implemented into the Koperasi Jasa Pratama system. The application that is made is then tested using the ISO 25010 standard to produce an optimal application. After conducting a needs analysis using the VORD method for ISO optimization, an application test is carried out using the ISO 25010 standard. From the test results, the characteristics of the Functional Suitability test are: Appropriate; Usability : 90.08; Performance Efficiency : Grade "B"; Portability : no errors. The test results show that the system is appropriate and feasible to use.